2019
DOI: 10.1021/acsaem.8b02253
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium-Ion Storage Capability of MXenes

Abstract: Rechargeable magnesium-ion batteries (MIBs) with Mg metal anodes have been attracting attention due to their potential safety, low cost, and high theoretical energy densities. Nevertheless, developing a high-energy-density MIB with long cycle life and reasonable rate capability is still a huge challenge due to the lack of high-performance cathodes beyond the Chevrel phases. Here, we investigate the mechanism of Mg-ion uptake and storage by MXenes, that have been theoretically predicted to be promising candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 67 publications
1
66
0
Order By: Relevance
“…It was demonstrated by Meng-Qiang Zhao et al regarding the storage of magnesium ions in MXenes. The asfabricated 3D microporous flexible and conductive MXene films were tested as a cathode in magnesium ion battery after the intercalation of magnesium ions from a magnesium-based electrolyte [79,80]. A fabricated composite Mg 0.21 Ti 3 C 2 T x electrode shows capacitance values of 210 mAh g −1 , 140 mAh g −1 and 55 mAh g −1 respectively at capacities of 0.5 C, 1 C, and 5 C. It was shown that after intercalating Mg 2+ ion between the MXene layers the (002) peak shifts from 6.5°to 5.7°.…”
Section: Effect Of Interlayer Distance Between Mxene Layers In Supercmentioning
confidence: 99%
“…It was demonstrated by Meng-Qiang Zhao et al regarding the storage of magnesium ions in MXenes. The asfabricated 3D microporous flexible and conductive MXene films were tested as a cathode in magnesium ion battery after the intercalation of magnesium ions from a magnesium-based electrolyte [79,80]. A fabricated composite Mg 0.21 Ti 3 C 2 T x electrode shows capacitance values of 210 mAh g −1 , 140 mAh g −1 and 55 mAh g −1 respectively at capacities of 0.5 C, 1 C, and 5 C. It was shown that after intercalating Mg 2+ ion between the MXene layers the (002) peak shifts from 6.5°to 5.7°.…”
Section: Effect Of Interlayer Distance Between Mxene Layers In Supercmentioning
confidence: 99%
“…A similar charge storage mechanism may be postulated for Mg-ions. However, the reported voltage profiles for non-aqueous Mg-electrolytes deviate and the charge-storage mechanism is far from resolved, [39][40][41] which will be discussed in the following.…”
Section: Structure Intercalation and Surface Reactionsmentioning
confidence: 99%
“…Another noteworthy attempt to enable MXene cathodes for RMBs was recently reported by Zhao et al, demonstrating a 3D macroporous Ti3C2Tx paper cathode with clear voltage plateaus and reversible capacities around 200 mA h g -1 . 41 The paper cathode was fabricated through a sacrificial template method, obtaining a porosity of around 90%. The highly porous paper was soaked in APC-THF, which lead to increased MXene d-spacing (from 1.36 to 1.55 nm) and substantial amounts of Mg, Al and Cl observed by EDX.…”
Section: Structure Intercalation and Surface Reactionsmentioning
confidence: 99%
See 2 more Smart Citations